Creating Cultural Monsters : Serial Murder in America. - Wiest, Julie B. (CRC Press, 2011)
Serial murderers generate an abundance of public interest, media coverage, and law enforcement attention, yet after decades of studies, serial murder researchers have been unable to answer the most important question: Why? Providing a unique and comprehensive exploration, Creating Cultural Monsters: Serial Murder in America explains connections between American culture and the incidence of serial murder, including reasons why most identified serial murderers are white, male Americans. It describes the omnipresence of serial murder in American media and investigates what it would take to decrea.